Recurrent Adult Sacrococcygeal Teratoma Developing Adenocarcinoma: A Case Report and Review of Literatures - Shengjie Cui; Jing Han; Binny Khandakar; Barak Friedman; Domingo Nunez; Gabriel A. Sara; Gabriel S. Levi (Hindawi Limited, 2021)
Sacrococcygeal teratomas (SCT) are most commonly seen in infants and children but are rare in adults. Most adult SCT are benign and mature with a minority of tumors having immature components or overt malignancy. Here, we report a 65-year-old female with a SCT developing adenocarcinoma. The patient was diagnosed with benign sacrococcygeal cystic teratoma on her initial hospital visit and was treated with surgical resection. She was followed up postoperatively and was noted to have a markedly elevated CA 19-9 level 13 months after the surgery. Radiological and clinical examination revealed thickening of the perirectal soft tissues, located near the inferior portion of her previous incision site. Histological evaluation of the lesion showed invasive, moderately differentiated adenocarcinoma. Immunohistochemical staining results were suggestive, but not diagnostic, of anal gland adenocarcinoma. This case report expands the knowledge regarding an adenocarcinoma arising from a previously benign, adult SCT.